External communication of automated shuttles: Results, experiences, and lessons learned from three European long-term research projects - Mirnig, Alexander G.; Gärtner, Magdalena; Fröhlich, Peter; Wallner, Vivien; Dahlman, Anna Sjörs; Anund, Anna; Pokorny, Petr; Hagenzieker, Marjan; Bjørnskau, Torkel; Aasvik, Ole; Demir, Cansu; Sypniewski, Jakub (Frontiers in Robotics and AI, 2022)
Automated shuttles are already seeing deployment in many places across the world and have the potential to transform public mobility to be safer and more accessible. During the current transition phase from fully manual vehicles towards higher degrees of automation and resulting mixed traffic, there is a heightened need for additional communication or external indicators to comprehend automated vehicle actions for other road users. In this work, we present and discuss the results from seven studies (three preparatory and four main studies) conducted in three European countries aimed at investigating and providing a variety of such external communication solutions to facilitate the exchange of information between automated shuttles and other motorized and non-motorized road users.